Reproductive ability of hybrids of Striga aspera and Striga hermonthica - Aigbokhan, E.I.; Berner, D.K.; Musselman, L.J. (1998)
Striga aspera and S. hermonthica are sympatric in Africa. Each may serve as virulent gene reservoirs for the other if they hybridize and their hybrids are virulent and fertile. Intraspecific and interspecific crosses were made within and between the species, and reproductive success was determined. Freshly harvested seeds from the parental and F1 crosses were tested over time for germination. Chromosome counts from shoottip squashes of seedlings of S. aspera were determined as n = 18, and as n = 19 for S. hermonthica. Hybridization results indicated that S. aspera and S. hermonthica could be intercrossed and their hybrids successfully backcrossed to either parent. Reproductive success in all crosses ranged from 68 to 95% and seeds of all the crosses were viable, germinated on exposure to a synthetic germination stimulant, and were pathogenic on maize. Seeds from the hybrids and backcrosses were less viable and germinable than either parent, suggesting that the two species were not 100% compatible. Results suggest that the two species are closely related, but are separate taxa, perhaps at the subspecies level. Seed dormancy for both species and the F1 hybrids was less than 84 days after pollination. Germination of S. hermonthica seeds reached 31% at 28 days after pollination. Frequently occurring seed germination peaks were observed for all the seeds tested.